Defective BiO2-x/BiOCl porous ultrathin nanosheets for efficient solar-light-driven photoreduction of Cr (VI). (15th June 2021) - Wu, Zhaohui; Li, Zhongfu; Wu, Min; Shen, Jie; Feng, Wenhui; Li, Xue; Xu, Difa; Zhang, Shiying; Ma, Nan
Abstract: It is inevitable to form invalid Type I heterostructure of BiOCl/bismuth-based photocatalysts due to the wide bandgap of BiOCl, which could only transfer the charge carriers efficiently, rather than separate. Herein, two-dimensional (2D) Type I van der Waals heterostructure of BiO2-x /BiOCl nanosheets were prepared through a solvothermal route, and massive defects and multiple pores were in-situ constructed on the BiO2-x /BiOCl nanosheets simultaneously. The defective and porous van der Waals structure of BiO2-x /BiOCl ultrathin nanosheets possessing enhanced internal electric field, induced defect level, and reduced interfacial barriers, promoting both efficient transfer and separation of charge carriers. Furthermore, the massive defects of BiO2-x /BiOCl porous nanosheets provided higher reactivity owing to its more hydrophilic surface. As a result, the BiO2-x /BiOCl nanosheets boosted the photocatalytic performance of Cr (VI) reduction and Rhodamine B (RhB) degradation when employing LED as simulated solar light. Based on the results, a plausible photocatalytic mechanism of Cr (VI) removal and RhB photodegradation was illustrated. We expected that this work could provide a feasible route to design distinctive heterostructure photocatalysts for improved photocatalytic performances under simulated solar light. Graphical abstract: Image 1